Tactical and statistical analysis of spiking efficiency by type, zone and set phase in women's volleyball - Sitti, Kiattisak; Rangubhet, K. Ravivuth (Frontiers in Sports and Active Living, 2025)
BackgroundSpiking is a decisive offensive action in elite women's volleyball, with variations in spike type, court zone, and timing influencing match outcomes. Understanding tactical and temporal dimensions of spiking can offer insights into offensive efficiency and performance consistency.MethodsA total of 2,599 spike attempts were analyzed from 29 matches (108 sets) in the 2024 Women's Volleyball Nations League. Each spike was categorized by type (straight, deep, diagonal, block-out, tip), attack zone (side vs. central), and set phase (early: Sets 1–2; middle: Set 3; endgame: Sets 4–5). Key performance indicators included kill rate, error rate, and efficiency index (EI). Comparative statistics were used to assess performance differences across match outcomes, spike types, zones, and phases.ResultsBlock-out spikes achieved the highest overall efficiency (EI = 0.79). Diagonal spikes showed significantly greater efficiency in winning sets (EI = 0.346) than in losing sets (EI = 0.147, p = 0.0198). Tip shots had the lowest efficiency (EI = 0.22) but the highest continuation rate (61%). Side zone attacks exhibited higher kill rates (25.2%) and efficiency (EI = 0.227) than central zone attacks (14.1% kill rate, EI = 0.106). Performance peaked during the middle set phase (EI = 0.318) but declined in the endgame phase (EI = 0.195; error rate = 0.151).ConclusionsSpike type selection, court positioning, and set phase timing significantly affect offensive performance. These insights can help coaches and analysts refine tactical planning, player rotation, and energy distribution strategies in elite women's volleyball.